Colocolic Intussusception in an Older Child: A Rare Case Report and a Literature Review - Anupam Das; Lalmalsawma Ralte; A. S. Chawla; S. V. Arya; Anil Kumar; Ravi Saroha; Dheer Singh Kalwaniya (Case Reports in Surgery)
Intussusception is a common cause of intestinal obstruction and colicky abdominal pain in the children, particularly infants, the commonest being the ileocolic variety with colocolic variety being a very rare entity. We present a case of colocolic intussusception in a 13-year-old boy which is otherwise seen in adults, precipitated by colonic malignancies. The patient presented with acute abdominal pain and bleeding perrectum with obstipation for 7 days. Preoperative USG abdomen was normal, and abdominal X-rays showed multiple air fluid levels. Intraoperative findings included a polypoidal growth in the descending colon as the leading point with the formation of a colo-colic intussusception. Following reduction and segmental resection, histopathology reported mucinous adenocarcinoma of colon which is also a rarity in pediatric age group. This case has been compared with previous cases reported in the literature.